METHODOLOGICAL APPROACHES TO THE STUDY OF THE MORAL AND AESTHETIC ESSENCE OF TOURISM (Scientific journal of the Fergana State University, 2026)
This article provides a comprehensive analysis of methodological approaches to studying the moral and aesthetic essence of tourism. Based on phenomenological, axiological, and cultural-philosophical perspectives, the paper explores the role of tourism in the moral, spiritual, and aesthetic development of individuals. Tourism is interpreted as a social phenomenon that fosters value formation, cultural integration, and personal growth. The study also examines the aesthetic experience and intercultural exchange processes emerging during travel. In the context of Uzbekistan, particular emphasis is placed on viewing tourism not merely as an economic sector but as a moral-aesthetic system that enhances human capital and strengthens social stability.